Pertanggungjawaban Hukum terhadap Pelaku Penyalahgunaan Data Pribadi: Studi Putusan Pengadilan Negeri Tangerang No.76/Pid.Sus/2024/PN Tng - Idris Wasahua (Jurnal Hukum Lex Generalis, 2025)
This study aims to examine the regulation of criminal acts involving the misuse of personal data under Law Number 27 of 2022 concerning Personal Data Protection, as well as the legal liability of perpetrators who misuse other individuals’ personal data as reflected in the Decision of the Tangerang District Court Number 76/Pid.Sus/2024/PN Tangerang dated April 2, 2024. This research is classified as normative legal research, employing a statutory approach, a conceptual approach, and a case approach. The results of this study indicate that the Personal Data Protection Law (PDP Law) provides a firm legal framework through Articles 67–70, which prohibit the unlawful acquisition, use, disclosure, and falsification of personal data, while also affirming that the protection of personal data constitutes a fundamental right that must be guaranteed by the state. The perpetrator’s actions in this case fulfilled all the elements of the charged provisions and therefore resulted in the imposition of criminal sanctions pursuant to Article 67 paragraph (3) of the PDP Law. Furthermore, the perpetrator’s conduct also satisfies the elements of an unlawful act as stipulated in Article 1365 of the Indonesian Civil Code, as such conduct violated the right to privacy, was committed intentionally, caused immaterial damage, and had a causal relationship with the harm suffered by the victim. Consequently, the perpetrator may also be held civilly liable under Article 1365 of the Indonesian Civil Code.